Teaching English To Young Learners: Learning Materials - Diyanti, B. Yuniar (Journal of English and Education (JEE), 2010)
Materials are important resources for teachers in assisting pupils to learn English. In broader view, materials can be defined as anything which is used specifically with the intention of increasing pupil's knowledge and experience of the language. Therefore materials may include textbooks (course books), workbooks, story books, videos, cassettes, pictures, brochures, menus, interactive CDs, or other real-life artifacts, (Moon, 2003: 86). In choosing and selecting materials for the teaching practices, we need to have several considerations like whether we have to create the materials ourselves, how we can select appropriate materials for our pupils, how we can adapt the materials in assisting our learners in learning, and what the benefits are of either adapting or creating our own learning materials. The article then aims at discussing these considerations in choosing, selecting, or creating learning materials in the teaching of English for your learners.